Patients' perceptions of telehealth video visits experience in primary healthcare setting, Saudi Arabia - Hanan F. Alotaibi; Sultan S. Ghazi; Nisreen O. Asraf; Zahra S. Al Asmari (Journal of Family Medicine and Primary Care)
Background: The widespread utilization of telehealth recently in Saudi Arabia is unprepared and may have a remarkable adverse effect on healthcare delivery. The study aimed to investigate attitude, satisfaction, and barriers of telehealth application among patients. Materials and Methods: A cross-sectional study was conducted at primary healthcare centers during the period of December 2021–January 2022. All Saudi patients (≥18 years) who were treated through telehealth programs in specialized polyclinic were eligible for study inclusion. A self-administered questionnaire was utilized and consists of four main parts: personal information, history of using telehealth, assessment of satisfaction with telehealth program, and attitude toward telemedicine. Results: A total of 641 participants were included. Females represented 57.3% of them. A majority (82.7%) of patients were satisfied with telemedicine services. Multivariate logistic regression analysis revealed that Bachelor/postgraduates were more likely to be satisfied with telemedicine services (P < 0.001), whereas patients reported no appointment slot in the clinic were less likely to be satisfied with telemedicine services (P = 0.042). A majority of patients (84.1%) expressed positive attitude toward telemedicine services. Multivariate logistic regression analysis revealed that older patients (P = 0.002) and widowed (P = 0.001) were less likely to have positive attitude toward utilization of telemedicine services, whereas Bachelor/postgraduates (P = 0.038) and patients with more than this time were more likely to have positive attitude toward telemedicine services (P = 0.001). Conclusion: Patients were overall satisfied and expressed positive attitude concerning the service of telemedicine consultation. However, more in-depth investigation is recommended to better understand the predictors of satisfaction with telemedicine and barriers for its proper application.